2022
DOI: 10.3390/brainsci12050554
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Neurophysiological and Neuropsychological Assessment of Patients with Left and Right Hemispheric Damage in Acute Ischemic Stroke

Abstract: The leading factors of post-stroke disability are motor disorders and cognitive dysfunctions. The aim of the study was to identify and provide a rationale for the variable early cognitive dysfunction in right and left hemispheric damage in patients with acute stroke. The study included 80 patients diagnosed with ischemic stroke. All patients were assessed for cognitive status, depression, fatigue and anxiety. For objectification, the method of evoked potentials (P300) and neuroimaging were used. Our findings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
2
5
0
1
Order By: Relevance
“…They are interrelated and have less to do with the location of the ischemic lesion and more to do with the lateralisation of the lesion and underlying neurodegeneration. P300-evoked potential analysis is a useful method for verifying cognitive impairment [27]. The presence of anxiety and depression with a total HADS score of at least 11 points was found in the qualitative assessment of these disorders, supporting the previous finding that patients with right-hemispheric stroke were more likely to experience anxiety than depression.…”
Section: Discussionsupporting
confidence: 80%
“…They are interrelated and have less to do with the location of the ischemic lesion and more to do with the lateralisation of the lesion and underlying neurodegeneration. P300-evoked potential analysis is a useful method for verifying cognitive impairment [27]. The presence of anxiety and depression with a total HADS score of at least 11 points was found in the qualitative assessment of these disorders, supporting the previous finding that patients with right-hemispheric stroke were more likely to experience anxiety than depression.…”
Section: Discussionsupporting
confidence: 80%
“…Twenty-nine studies ( n = 3709 participants) assessed whether lesion lateralization was associated with PSF. 9 , 16 43 Of these, 24 showed no association, 3 reported a higher prevalence of PSF with right-sided stroke, 29 , 34 , 38 and 1 showed a higher prevalence of PSF in right-sided stroke at 6-month follow-up but not at baseline. 43 One study reported higher rates of general and mental fatigue in those with left-sided lesion lateralization.…”
Section: Resultsmentioning
confidence: 95%
“… 43 One study reported higher rates of general and mental fatigue in those with left-sided lesion lateralization. 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the latency of P300 is a more sensitive index than amplitude in patients with stroke ( 21 , 29 ). Some studies have found that the latency of P300 in patients with vascular cognitive impairment is significantly prolonged, but the amplitude of P300 has no significant difference from that of normal subjects ( 30 ). The results of this study confirmed that P300 latency is a sensitive index to detect the improvement of cognitive function in patients with PSCI from the point of view of cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%